Caracterização química e estudo térmico de lodos provenientes da estação de tratamento de esgotos de Ribeirão Preto, SP, Brasil - Santos, Danilo Vitorino dos [UNESP] (2014)
Nowadays, the environmental degradation is a major concern and brings up great concern about the impact that urban pollution can cause to the environment and human health. In search of the decontamination of urban wastewater, the Sewage Treatment Plants (STP) play a major role in environmental preservation and promote increase in population's quality of life, however, as an intrinsic product of the wastewater treatment process, solid waste (sludge) are generated in large quantities and can represent high environmental impact. This work presents a detailed characterization of this kind of residues, including a thermal and kinetic study of this matrix. The analyzed samples of sludge come from each step of sludge line (thickener, flotator, biodigester and storage shed) of Ribeirão Preto STP. The study was conducted employing analysis (TGA, DTA and DSC) and complementary techniques such as: COD, XRD, SEM/EDS, DLS, FTIR, AAS, elemental analysis (CNHS-O) and GC-FID/TCD. The kinetic parameters (E and A) and KCE was determined using the method analogous to the Wanjun and Donghua isoconversional integral method. The results of COD showed that the sludge samples have large amounts of organic matter (OM). The XRD data also confirm this result, characterizing the amorphous state of matter. SEM/EDS results showed the occurrence of heterogeneous, irregular and porous surfaces; wide variety of particles with spherical and filamentous structures consisting of mainly C, O, Ca, Si, P, Al and Fe. The data obtained from DLS revealed that the sludge particles have sizes ranging from 78 - 6440 nm. FTIR analysis revealed the presence of the following functional groups: OH (water, phenols, alcohols); CH (aliphatic); C=O (ketones, quinones, carboxylic acids and carboxylates coordinated with metals); CN and C=C (aromatics); C=O, NO and SO (carboxylates, nitrates and sulfates); C=O, SO, OC=O and SiO...